Water Carrying Capacity on Small Islands Tourism: Case Study of the Tidung Islands, Jakarta - Basyar Ihsan Arijuddin (Jurnal Syntax Admiration, 2024)
This study examines the water carrying capacity of the Tidung Islands, a popular small island tourism destination in Jakarta, Indonesia. The research aims to measure the availability of water resources and assess the balance between water supply and demand, focusing on both domestic and tourism needs. Using a water balance approach, the study analyzes seasonal fluctuations in precipitation, evapotranspiration, runoff, and changes in water storage. The results indicate that while Tidung Islands currently have a surplus of water resources, projected increases in population and tourism will lead to periods of water deficit by 2040. The study highlights the critical need for sustainable water management practices, including rainwater harvesting, efficient water use, and community involvement in conservation efforts. Implementing these strategies is essential to ensure long-term water security and support the continued growth of tourism and local development in Tidung Islands.